The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1sc02450g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metallosupramolecular polymer concentration on the synthesis of poly[n]catenanes

Abstract: Concentration of the metallosupramolecular polymer precursors have a significant effect on the architecture and size of the resulting poly[n]catenanes formed via a ring closing metathesis step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…2 equiv., see ESI, Fig. S2 †) and the mixture was equilibrated for 1 day at 45 C. Aer equilibration, the 1 H-NMR spectrum simplied and, using previously published 1 H NMR spectra of doubly threaded metal-templated Bip complexes, [87][88][89] it is possible to assign each resonance peak to a given proton in the complex (Fig. 1 and 2b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 equiv., see ESI, Fig. S2 †) and the mixture was equilibrated for 1 day at 45 C. Aer equilibration, the 1 H-NMR spectrum simplied and, using previously published 1 H NMR spectra of doubly threaded metal-templated Bip complexes, [87][88][89] it is possible to assign each resonance peak to a given proton in the complex (Fig. 1 and 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of such upeld shied peaks imply these protons are in a more shielded environment, and would be consistent with an interlocked structure. [87][88][89] A MALDI-TOF MS spectrum (see ESI, Fig. S12 †) of the reaction mixture recorded aer 6 minutes in solution conrmed only the presence of 1 and 6, with no signals indicative of [3]rotaxane 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggested that the MSP was present in both the linear and cyclic form, the ratio of which depends on the reaction concentration. 72 Ring closing the thread component in the MSP was achieved through olefin metathesis of its alkene tails resulting in a mixture that contains the metalated poly[ n ]catenanes. Removal of the metal ion yielded the desired poly[ n ]catenane 30 , along with some non-interlocked species.…”
Section: Methods Utilized For the Synthesis Of Polycatenanesmentioning
confidence: 99%
“…In these high concentration reactions, evidence from MALS suggests the presence of poly[n]catenanes with up 640 interlocked rings (1000 kg mol À1 ). 72 As a consequence of the metal ion templating employed in the synthesis of the poly[n]catenanes, 30 exhibits stimuli-responsive behaviour. When the ligand moieties in these catenanes are not complexed to metal ions, the rings are mobile; however, adding in the metal ions results in the reformation of the metal-ligand complexes and a locking in of the catenane units.…”
Section: Ring Closing As the Polymerization Stepmentioning
confidence: 99%